Cytokine and Adhesion Molecule Expression Induced by Different Strains of Staphylococcus aureus in Type 1 Diabetic Rats: Role of Insulin - de Souza, Paula R. Knox; Ferreira, Sabrina S.; Nunes, Fernanda P. B.; Casagrande, Felipe B.; Tessaro, Fernando H. G.; Silva, Mariana C. F.; Cruz, José Walber Miranda Costa; Mamizuka, Elsa M.; Martins, Joilson O. (Frontiers in Immunology, 2019)
Introduction: Staphylococcus aureus may provoke peritonitis and death, especially in immunocompromized individuals such as diabetic patients. We evaluated the role of insulin in S. aureus-induced peritoneal infection in diabetic and non-diabetic rats. Materials/Methods: Alloxan-diabetic male Wistar rats and their respective controls received intraperitoneal injections of different strains of S. aureus or sterile phosphate-buffered saline. After three days of infection, the first set of diabetic and non-diabetic rats received 4 and 1 IU, respectively, of neutral protamine Hagedorn insulin and were analysed 8 h later. The second set of diabetic and non-diabetic rats received 4 and 1 IU, respectively, of insulin 2 h before intraperitoneal infection and a half dose of insulin at 5 pm for the next 2 days and were analysed 16 h later. The following measurements were performed: a) number of cells in the peritoneal lavage fluid (PeLF), white blood cell count and blood glucose; b) serum insulin and corticosterone; c) cytokine levels in the PeLF; d) expression of adhesion molecules in the vascular endothelium; and e) microbicidal activity. Results: Diabetic rats showed an increased number of polymorphonuclear leukocytes (PMNs) and increased concentrations of CINC-1, IL-4 and IFN-γ in the PeLF after infection with the ATCC 25923 or N315 HL+ strain. The mesenteric expression of PECAM-1 was increased after infection with the N315 HLA+ strain. ICAM-1 expression was increased with ATCC infection. Treatment of diabetic rats with a single dose of insulin restored CINC-1 levels in the PeLF for both strains; however, PMN migration, IL-4 and IFN-γ were restored in rats infected with the ATCC strain, whereas the PeLF concentrations of CINC-2, IL-1β and IL-4 were increased in N315-infected animals. Insulin restored PMN migration and CINC-2 levels in the PeLF in ATCC-infected rats. After multiple treatments with insulin, the levels of IL-1β, IL-6 and IFN-γ were increased in the PeLF of diabetic rats after infection with either strain, and CINC-2 levels were restored in N315-infected animals. Conclusion: These results suggest that insulin distinctively modulates cytokine production or release, PMN leukocyte migration and adhesion molecule expression during the course of peritonitis induced by different strains of S. aureus.